Chronic osteomyelitis of clavicle in a 25 year-old male - Chaudhary, P; Karn, NK; Shrestha, BP; Khanal, GP; Maharjan, R (Health Renaissance, 2011)
Osteomyelitis of clavicle is very uncommon. The most common locations include metaphysic of long bones.1 Here, we present a case of 25 year old male who had presented to the Orthopaedic department of B.P. Koirala Institute of Health Sciences, Dharan, Nepal with complain of pain and Chronic discharging sinus from left clavicle for last 1 year. There was history of abscess over the clavicle and incision and drainage was performed 1 year back by the general surgeon. With all these characteristics and literature reviewed, we report this case for its rarity and unique characteristics. In this part of world (Nepal) patients commonly present late to the hospital DOI: http://dx.doi.org/10.3126/hren.v9i2.4988 Health Renaissance 2011: Vol.9 (No.2): 125-127